Engineering strategies for enhanced heterologous protein production by Saccharomyces cerevisiae - Meirong Zhao; Jianfan Ma; Lei Zhang; Haishan Qi (Microbial Cell Factories, 2024)
Abstract Microbial proteins are promising substitutes for animal- and plant-based proteins. S. cerevisiae, a generally recognized as safe (GRAS) microorganism, has been frequently employed to generate heterologous proteins. However, constructing a universal yeast chassis for efficient protein production is still a challenge due to the varying properties of different proteins. With progress in synthetic biology, a multitude of molecular biology tools and metabolic engineering strategies have been employed to alleviate these issues. This review first analyses the advantages of protein production by S. cerevisiae. The most recent advances in improving heterologous protein yield are summarized and discussed in terms of protein hyperexpression systems, protein secretion engineering, glycosylation pathway engineering and systems metabolic engineering. Furthermore, the prospects for efficient and sustainable heterologous protein production by S. cerevisiae are also provided.